THE IMPACT OF WORK MOTIVATION ON TEACHER PERFORMANCE THROUGH WORK DISCIPLINE AT THE ARRIYADLAH FOUNDATION IN PROBOLINGGO - Moh. Najiburrahman; Harsono; Sugeng Haryanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study delves into the intricate relationship between work motivation, work discipline, and teacher performance within the Arriyadhlah Foundation in Probolinggo, Indonesia. It explores how these crucial factors interact to shape the foundation's educational landscape and foster excellence in teaching. The aim of this research is Analyze the influence of work motivation on teacher performance at the Arriyadhlah Foundation, Investigate the role of work discipline in mediating the relationship between motivation and performance, and Evaluate the specific context of the Arriyadhlah Foundation. Surveys will be administered to teachers to assess their levels of work motivation, perceived work discipline, and self-reported performance indicators. Statistical analysis will be conducted to identify any significant correlations between these variables. By examining the specific context of the Arriyadhlah Foundation and its commendable commitment to high-quality education, this study will offer valuable insights applicable not only to Indonesia but also to educational institutions worldwide. It will contribute to the ongoing conversation about teacher motivation, work discipline, and their combined impact on creating effective learning environments and fostering student success.